2005
DOI: 10.1207/s15327558ijbm1203_2
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial considerations in the european guidelines for prevention of cardiovascular diseases in clinical practice: third joint task force

Abstract: The International Society of Behavioral Medicine (ISBM) was one of eight societies that comprised the Third Task Force of European and Other Societies on Prevention of Cardiovascular Disease in Clinical Practice (2003-2004). This task force considered published knowledge from diverse fields related to preventive cardiology including behavioral medicine to improve risk estimation and risk factor management. The scientific evidence supporting the guidelines included findings on low socioeconomic status, social i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 88 publications
0
26
0
Order By: Relevance
“…This finding is important in the acute cardiac care and rehabilitation context, given that guidelines for the assessment of psychosocial risk factors in coronary heart disease recommend exploring depression and hostility but not anxiety, 36 and only recently were cardiac-rehabilitation recommendations refined to advocate psychosocial evaluations of anxiety in addition to depression. 37 Recent CABG studies showed that anxiety is associated with myocardial infarction and mortality 19,38 and unplanned hospital readmissions, 22 suggesting, in conjunction with our findings, that hospital staff should consider patient self-reported anxiety as an important correlate of morbidity, including AF, after CABG.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is important in the acute cardiac care and rehabilitation context, given that guidelines for the assessment of psychosocial risk factors in coronary heart disease recommend exploring depression and hostility but not anxiety, 36 and only recently were cardiac-rehabilitation recommendations refined to advocate psychosocial evaluations of anxiety in addition to depression. 37 Recent CABG studies showed that anxiety is associated with myocardial infarction and mortality 19,38 and unplanned hospital readmissions, 22 suggesting, in conjunction with our findings, that hospital staff should consider patient self-reported anxiety as an important correlate of morbidity, including AF, after CABG.…”
Section: Discussionmentioning
confidence: 99%
“…Depressive symptoms were assessed by three items only. This may be an acceptable screener for depressive symptoms (Orth-Gomér et al 2005) but it is far from providing a diagnosis. However, Meyer et al (2007) have presented results from the same data base on the association between depression and low back pain that are in favour of the validity of the items used here.…”
Section: Strength and Limitations Of This Studymentioning
confidence: 99%
“…Finally, it will be important to continue simulating the conditions of Westernized society that are associated with increased or excessive consumption of high energy density, highly palatable foods. Although most citizens in Westernized societies currently face little stress in the form of predators or chronic adverse physical conditions, psychological stressors are common in U.S. and European society (54) and thus the addition of a chronic or semi-chronic psychological stress component to studies of food reward should provide valuable new insight into modulation of food reward and reinforcement (55). These studies may be more technically difficult but they will be critical for true translation from what is learned in the laboratory regarding 'food reward', into potentially relevant insights for therapeutic application to the feeding habits and patterns of societies confronted with an obesity epidemic.…”
Section: Future Directions For Food Reward Researchmentioning
confidence: 99%